The Co-movement of Asset Returns and the Micro-Macro Focus of Prudential Oversight - Majnoni, Giovanni (2012)
The integration of micro-prudential oversight with the macro-approach to financial stability -- long in the making -- raises several issues of coordination of regulatory responsibilities. This paper argues that a decomposition of the covariance of asset returns into an endogenous volatility component -- which can be reduced -- and an exogenous volatility component -- which we have to live with -- helps address these coordination issues and provides the basis for financial health diagnostics and supervisory responses to observed symptoms of financial instability. By linking risk origination and risk control, the paper may also contribute to the search for an operational definition of the term "macro-prudential."